2017
DOI: 10.1002/sdtp.11605
|View full text |Cite
|
Sign up to set email alerts
|

21‐1: Development of 55” 4K UHD OLED TV Employing the Internal Gate IC with High Reliability and Short Channel IGZO TFTs

Abstract: We investigated oxide TFT backplane technology to employ the internal gate driver IC (GIP circuit) on 55” 4K OLED TV panel. For the GIP circuit, we developed the high reliability oxide TFTs, especially only ∆0.4V Vth degradation under 100‐hour long‐term PBTS stress and the short channel length TFTs (L=4.5um) for narrow bezel (5.5mm). Consequently, we demonstrated the 55‐in 4K OLED TV employing the internal gate IC with high reliability and short channel IGZO TFTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Slightly larger Vth variation and non-uniformity are observed from higher temperature and/or lower RF power due to more hydrogen partial diffusion during GI deposition than lower temperature and/or higher RF power. From previous reports, larger amount of oxygen vacancies at the interface between GI and IGZO or in IGZO are significantly changing threshold voltages as channel length become less than 10 µm, which make IGZO channel in TFTs more conductive as a cause of negative Vth shift [2,3]. The impact of oxygen vacancies become stronger as channel length become smaller.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Slightly larger Vth variation and non-uniformity are observed from higher temperature and/or lower RF power due to more hydrogen partial diffusion during GI deposition than lower temperature and/or higher RF power. From previous reports, larger amount of oxygen vacancies at the interface between GI and IGZO or in IGZO are significantly changing threshold voltages as channel length become less than 10 µm, which make IGZO channel in TFTs more conductive as a cause of negative Vth shift [2,3]. The impact of oxygen vacancies become stronger as channel length become smaller.…”
Section: Resultsmentioning
confidence: 91%
“…AMOLED displays employing GIP TFTs also needs to use shorter channel length of TFTs to reduce device size for narrow display bezel and to increase drainto-source current (IDS) for low voltage and low power operations. J. Y. Noh, et al demonstrated 5.5 mm-thick narrow bezel 55" 4K UHD AMOLED TVs employing GIP circuits with 4.5 µm channel length IGZO TFTs by optimizing ∆L (the oxygen vacancies diffusion length from n+ IGZO region to channel region) [2]. However, further reduction of channel length less than 4.5 µm in GIP TFTs is preferred but is not easy due to larger ∆L and Vth negative shift with larger Vth non-uniformity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxide TGSA backplane we fabricated requires 9 masks. Ti metal shading layer is deposited on the glass substrate by Sputter to avoid the impact of ambient light on the channel, Then SINx/SIO2 buffer layer is deposited by PECVD, the high mobility semiconductor IGZTO layer is deposited above the buffer layer, the material mobility can reach more than 20cm2/V•s [2]. SIO2 gate insulation layer is deposited.…”
Section: Device Fabricationmentioning
confidence: 99%
“…The amorphous indium gallium zinc oxide (a-IGZO) TFT has been regarded as a promising backplane technology for developing large size high resolution displays, including liquid crystal displays (LCDs) and organic light emitting diode (OLED) displays [1], [2]. Compared to amorphous silicon TFTs, the a-IGZO TFT owns much improved mobility and operational stability, while maintaining similar processing complexity and device uniformity suitable for large area and low-cost manufacturing [3], [4].…”
Section: Introductionmentioning
confidence: 99%